(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background: Needle Stick Injuries(NSI) are accidental skin penetrating injuries by sharp medical instruments to healthcare professionals which may transmit infections or diseases. This occupational injury needs to be addressed seriously. We conducted a cross sectional study regarding prevalence and awareness of NSI among medical and paramedical professionals. Objectives : To assess the awareness of medical and paramedical professionals regarding Needle Stick Injuries and related aspects. To discover the prevalence of needle stick injuries in medical and paramedical professionals. Materials & Methods: We conducted a cross sectional observational study with pre-validated questionnaire. Total 100 participants were enrolled as per inclusion and exclusion criteria.